2019
DOI: 10.3390/nu11122883
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition as a Strong Predictor of the Onset of Sarcopenia

Abstract: This study aims to explore the association between malnutrition diagnosed according to both the Global Leadership Initiative of Malnutrition (GLIM) and the European Society of Clinical Nutrition and Metabolism (ESPEN) criteria and the onset of sarcopenia/severe sarcopenia, diagnosed according to the European Working Group on Sarcopenia in Older People 2 (EWGSOP2) criterion, in the sarcopenia and physical impairment with advancing age (SarcoPhAge) cohort during a four-year follow-up. Adjusted Cox-regression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
134
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 156 publications
(155 citation statements)
references
References 49 publications
6
134
1
1
Order By: Relevance
“…According to the GLIM framework, 46% of patients were identified as malnourished when using combinations of two criteria. This prevalence could be apparently high as compared with previous studies which used the GLIM criteria for the diagnosis of malnutrition [5,[25][26][27]. Nevertheless, this investigation focused on a special population that presented with a high prevalence of etiologic GLIM criteria for malnutrition.…”
Section: Discussionmentioning
confidence: 86%
“…According to the GLIM framework, 46% of patients were identified as malnourished when using combinations of two criteria. This prevalence could be apparently high as compared with previous studies which used the GLIM criteria for the diagnosis of malnutrition [5,[25][26][27]. Nevertheless, this investigation focused on a special population that presented with a high prevalence of etiologic GLIM criteria for malnutrition.…”
Section: Discussionmentioning
confidence: 86%
“…38,39 Data from our research group indicate that GLIM criteria are also strong predictors of the onset of sarcopenia, as they were associated with an approximately four-fold higher risk of developing sarcopenia and severe sarcopenia during a 4-year follow-up. 40 Surprisingly, no association was found between malnutrition and institutionalization, hospitalization, falls, and fractures. This lack of association might be a bias due to the 45 subjects lost to follow-up, who were not included in the analyses; those individuals who were more likely to present adverse health consequences might have been lost for the analysis.…”
Section: Discussionmentioning
confidence: 98%
“…Vincenzo et al found that malnutrition increased the incidence of sarcopenia in older adults, MNA-SF (OR = 0.57, 95% CI 0.34-0.96) was one of the related factors associated to sarcopenia [37]. Similarly, the risk of developing sarcopenia in elderly patients with poor nutritional status almost a fourfold increase according to a study conducted by Charlotte et al [38].…”
Section: Discussionmentioning
confidence: 95%